A method for preparing a nitriding-TiN composite coating with mechanical and biological properties on a medical metal surface
Patent Information
- Application Number
- CN202410435186.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-11
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-04-11
AI Technical Summary
高能离子沉积可能会导致吸附-脱附现象,此过程中表面原子可能发生脱附,降低涂层的沉积速率,这是高功率脉冲磁控溅射技术目前需要解决的问题之一
[0024] I. Currently, medical implants such as total hip arthroplasty, dental implants, and coronary artery stents still face the risk of failure in clinical practice. The main reasons are foreign body reactions caused by implant wear debris and corrosion products, as well as bacterial infections. This invention provides a method for preparing a composite coating with excellent mechanical and biological properties through low-pressure plasma nitriding and coating deposition. A special combined process is employed to coordinate and control multiple key preparation parameters, such as temperature and gas pressure during ion cleaning, substrate negative bias, various gas flow rates, sputtering target power, magnetic field strength, and target-substrate distance during deposition. This achieves technological fusion, maximizing the combined advantages of these technologies. The resulting TiN coating, possessing excellent biocompatibility, antibacterial adhesion, and wear resistance, is deposited on the implant surface to specifically enhance implant performance and improve its durability.
Smart Images

Figure CN118531341B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal composite coatings, and in particular to a method for preparing a nitrided-TiN composite coating and a composite coating that possesses both mechanical and biological properties on a metal surface. Background Technology
[0002] Medical implants such as total hip arthroplasty, dental implants, and coronary artery stents are widely used in clinical practice, but they still face the risk of implant failure. Foreign body reactions caused by implant wear debris and corrosion products, as well as bacterial infections, are the main factors leading to implant failure. Depositing coatings on the implant surface is an effective strategy to enhance implant performance and improve its durability. To date, surface coating modification of implants is a research hotspot in the field of biomedical materials. TiN coatings possess good biocompatibility, high wear resistance, and corrosion resistance, making TiN coating deposition on the surface of metallic implants an effective strategy to address their performance shortcomings.
[0003] The performance of hard coatings on substrate materials is affected by load conditions and residual stress during service. Due to deficiencies in load-bearing capacity, plastic deformation, and bonding strength, coating-substrate systems are prone to "eggshell failure."
[0004] The existing patent, titled "A Titanium Alloy Surface Coating and Its Preparation Method," application number CN202210780484.0, describes a method comprising: pretreating the surface of a titanium alloy substrate; preparing a chitosan coating on the pretreated titanium alloy substrate surface using a constant potential electrochemical deposition method with a chitosan solution as the electrolyte; and preparing a hydroxyapatite coating on the chitosan coating surface using a constant potential electrochemical deposition method with a solution containing calcium and phosphate ions as the electrolyte. This invention uses a constant potential electrochemical deposition method to sequentially prepare a chitosan coating and a hydroxyapatite coating on the surface of a biomedical titanium alloy, resulting in a titanium alloy with a bilayer coating of chitosan and hydroxyapatite. This alloy not only exhibits excellent biocompatibility, antibacterial properties, and corrosion resistance, but also demonstrates mechanical properties that match those of bone. However, the electrochemical deposition method is technically challenging and costly, making it impractical for widespread application, and the coating adhesion and wear resistance are not high.
[0005] In existing technologies, plasma-assisted arc technology, utilizing high-current-density cathode-anode arc discharge, can generate a large number of high-energy deposited particles. However, the high current density and high-energy arc discharge easily melt the target material in a small area, leading to the formation of micron-sized (1–25 μm) droplets and large particles on the coating surface. This is a limitation of plasma-assisted arc technology. High-power pulsed magnetron sputtering is a relatively new PVD technology. The high-power pulse causes significant ionization of the metal target, and the ionized ions bring significant kinetic and potential energy to the coating growth process. The particle energy range includes tens or even hundreds of electron volts (eV), which usually exceeds the displacement energy of atoms near the surface. High-energy ion deposition may lead to adsorption-desorption phenomena, during which surface atoms may desorb, reducing the coating deposition rate. This is one of the problems that high-power pulsed magnetron sputtering technology currently needs to solve. Existing coating processing technologies, due to the difficulty in controlling parameters and the difficulties in actual operation, cannot achieve optimal results in terms of adhesion, wear resistance, biocompatibility, and antibacterial properties of nitrided-TiN coatings. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a nitriding-TiN composite coating on medical metal surfaces that possesses both mechanical and biological properties. This method is practical and easy to operate, and can comprehensively improve the adhesion, wear resistance, biocompatibility, and antibacterial adhesion of the nitriding-TiN coating on medical metal surfaces. Medical metals with the nitriding-TiN coating of this invention are used in medical metal implants, maintaining excellent biocompatibility and antibacterial adhesion while significantly improving the wear resistance and durability of the implant. They are mainly used in artificial joints, dental implants, etc.
[0007] This invention provides a method for preparing a nitrided-TiN composite coating with both mechanical and biological properties on a medical metal surface, comprising the following steps:
[0008] (1) Substrate preparation and pretreatment: After grinding and polishing, the substrate is placed in anhydrous ethanol for ultrasonic cleaning. The air-dried substrate is sent into the coating equipment chamber and the moisture, trace gases and volatile impurities adsorbed on the substrate surface are removed by repeated heating and vacuuming.
[0009] (2) Ion cleaning: The substrate is ion cleaned using arc-enhanced glow discharge technology. The cathode target is a Ti target with a purity of 99.99%. High-purity Ar is introduced to maintain the chamber pressure at 1×10⁻⁶. -4 ~1×10 -2 mbar;
[0010] (3) Low-pressure plasma nitriding treatment: The substrate is nitrided using arc plasma-assisted nitriding technology. High-purity N2, high-purity H2 and high-purity Ar are continuously introduced into the chamber at the same time. The appropriate gas pressure and temperature in the chamber are kept constant. The substrate is subjected to negative bias and plasma nitriding treatment for 45 to 90 minutes.
[0011] (4) In-situ integrated coating treatment: A TiN composite coating with excellent biocompatibility and antibacterial adhesion is prepared on the surface of the nitrided substrate by using high-power pulsed magnetron sputtering technology or a hybrid deposition coating technology of plasma-assisted electric arc and high-power pulsed magnetron sputtering.
[0012] Preferably, in step (1), the chamber is heated and evacuated twice, first by evacuating the chamber to a vacuum level of 4.0 × 10⁻⁶. -5 Below mbar, heat at 550–600℃ for 30–60 minutes, then evacuate the chamber to a vacuum of 4.0 × 10⁻⁶ mbar. -5 Below mbar, heat at 500–550℃ for 30–60 minutes.
[0013] Preferably, in step (2), the planetary carrier bipolar bias voltage used in ion cleaning is -200 to -300 / +20V, the target current is 65 to 95A, the temperature is 300 to 600℃, and the duration is 5 to 20 minutes.
[0014] Preferably, in step (3), high-purity N2, high-purity H2, and high-purity Ar are continuously introduced into the chamber while maintaining a suitable constant gas pressure (0.15–2.0 Pa) and temperature (450–600 °C) within the chamber. A negative bias voltage (-50–-400 V) is applied to the substrate, and plasma nitriding treatment is performed for 45–90 minutes. The purity of the high-purity N2, high-purity H2, and high-purity Ar is all 99.99%.
[0015] Preferably, in step (3), the arc target that serves as the electron source is a Ti target with a purity of 99.99% and a target current of 65-95A; the planetary carrier on which the substrate is placed is connected to the negative terminal of the pulse power supply with a negative bias voltage of -50 to -400V, using a bipolar pulse with a frequency of 15-25kHz and a duty cycle of 65%-95%.
[0016] The ion nitriding temperature is 450–600℃, the gas pressure is 0.15–2.0 Pa, the N2 flow rate is 20–55 sccm, the H2 flow rate is 20–55 sccm, and the Ar flow rate is controlled by the gas pressure to be 120–190 sccm.
[0017] Preferably, in step (4), when high-power pulsed magnetron sputtering (HiPIMS) is used for coating, the sputtering target is a Ti target with a purity of 99.99%, the working gas is Ar with a purity of 99.99% and N2 with a purity of 99.99%; the target-substrate distance is controlled to be 85-90 mm, the gas input during coating is controlled by flow rate, the total flow rate is maintained at 130-180 sccm, the average power is 5-7 kW, the pulse on-time and pulse off-time are 20-60 / 1000 μs, the magnetic field strength is 45-50 mT, the substrate bias voltage is -100--300 V, the temperature of the infrared heating tube is set to 400-550 °C, and the deposition time is 120-240 min.
[0018] Preferably, in step (4), when a hybrid deposition coating of plasma-assisted arc (APA-Arc) and high-power pulsed magnetron sputtering (HiPIMS) is used, the deposition rate and high particle incident energy are improved. Both the sputtering target and the arc target are Ti targets with a purity of 99.99%, the working gas is Ar with a purity of 99.99%, and the target-substrate distance is 85-90 mm. The hybrid deposition coating includes an APA-Arc deposition process, an APA-Arc and HiPIMS co-deposition process, and a HiPIMS deposition process.
[0019] Preferably, in step (4), during the APA-Arc deposition process, the substrate bias voltage is -50 to -300V, the target current is 100 to 140A, the deposition time is 40 to 70Ah, the N2 flow rate is 35 to 70sccm, and the Ar flow rate is controlled so that the total gas pressure is 0.9 to 1Pa.
[0020] During the co-deposition of APA-Arc and HiPIMS, the matrix bias voltage is -200 to -300V, the deposition time is 70 to 110Ah, the N2 flow rate is 40 to 70sccm, and the Ar flow rate is controlled to make the total gas pressure 0.9 to 1Pa.
[0021] During the HiPIMS deposition process, the average power is 3–7 kW, the pulse on-time and pulse off-time are 20–60 / 1000 μs, the magnetic field strength is 45–50 mT, the substrate bias voltage is -50–-300 V, the infrared heating tube temperature is set to 400–550 °C, the deposition time is 60–120 min, the N2 flow rate is 20–40 sccm, and the Ar flow rate is controlled to make the total gas pressure 0.55–0.68 Pa.
[0022] This invention also provides a medical metal with a nitriding-TiN composite coating on its surface, the nitriding-TiN composite coating being prepared using the method described above. The medical metal substrate is austenitic stainless steel, titanium, or a metal alloy, used in medical metal implants, which maintains excellent biocompatibility and antibacterial adhesion while significantly improving the wear resistance and durability of the implant. When a hybrid deposition coating is performed using plasma-assisted arc (APA-Arc) and high-power pulsed magnetron sputtering (HiPIMS), the nitriding-TiN composite coating exhibits a three-layer microstructure.
[0023] Compared with traditional preparation methods, the beneficial effects of the present invention are as follows:
[0024] I. Currently, medical implants such as total hip arthroplasty, dental implants, and coronary artery stents still face the risk of failure in clinical practice. The main reasons are foreign body reactions caused by implant wear debris and corrosion products, as well as bacterial infections. This invention provides a method for preparing a composite coating with excellent mechanical and biological properties through low-pressure plasma nitriding and coating deposition. A special combined process is employed to coordinate and control multiple key preparation parameters, such as temperature and gas pressure during ion cleaning, substrate negative bias, various gas flow rates, sputtering target power, magnetic field strength, and target-substrate distance during deposition. This achieves technological fusion, maximizing the combined advantages of these technologies. The resulting TiN coating, possessing excellent biocompatibility, antibacterial adhesion, and wear resistance, is deposited on the implant surface to specifically enhance implant performance and improve its durability.
[0025] II. Regarding the modification of surface coatings for medical implants, the traditional method involves directly depositing a TiN coating on the surface of stainless steel, titanium, or titanium alloys using PVD. This can lead to problems such as insufficient coating adhesion and susceptibility to cracking and delamination during fretting and wear within the body. This invention combines the high degree of compatibility between the nitriding layer and the TiN coating in terms of hardness, internal stress, and phase structure. Before depositing the TiN coating, the substrate is pretreated using low-pressure plasma nitriding technology. This allows the substrate and coating to form an integral hardness and composition gradient structure, thereby significantly improving the coating adhesion.
[0026] In traditional ion nitriding technology, the gas discharge occurs in the abnormal glow discharge region, but the discharge is unstable, with high voltage and current, which can easily lead to excessively high local temperatures and damage to the workpiece, resulting in unsatisfactory nitriding effects. Unlike the glow discharge of traditional nitriding, the low-pressure plasma nitriding technology of this invention takes a unique approach, utilizing arc discharge, resulting in low nitriding gas pressure (0.4–4 Pa) and high plasma density (10⁻⁶ Pa). 10 ~10 11 cm -3The coating adhesion (around 50N) prepared by this invention is much higher than the adhesion requirement (greater than 10N) for coatings on the surface of medical implants.
[0027] Third, traditional PVD coating technologies, such as arc ion plating, are prone to defects such as pits and large droplets in the deposited coating. These defects accelerate local damage during joint movement and can easily become corrosion and oxidation sites, making the coating easy to delaminate and peel off from the implant surface, causing foreign body reactions and bacterial infections.
[0028] The present invention provides two coating preparation techniques. The first technique is an improved high-power pulsed magnetron sputtering (HiPIMS) technology, which produces a coating with extremely high surface smoothness and excellent uniformity. The low surface roughness makes it difficult for bacteria to adhere, while the high surface energy is more conducive to the adhesion and proliferation of human bone marrow mesenchymal stem cells. The second technique is a hybrid deposition coating scheme that combines the advantages of plasma-assisted arc technology and high-power pulsed magnetron sputtering technology. The arc technology boasts a high deposition rate and high particle incident energy, resulting in a denser coating structure and stronger bonding. This hybrid multi-layer deposition coating technology, while ensuring good coating quality, effectively shortens the deposition time compared to existing magnetron sputtering technologies when depositing coatings of the same thickness. These two coating preparation techniques each endow the coating with unique performance characteristics.
[0029] Fourth, the optimization and control of key process parameters in this invention can control the chemical composition and surface nanomorphology of the TiN coating, and comprehensively improve the adhesion, wear resistance, biocompatibility and antibacterial adhesion of the TiN coating. Therefore, the TiN coating modified metal implant prepared by this invention has great commercial potential. Attached Figure Description
[0030] Figure 1 The images show the AFM morphology of the TiN sample and the titanium substrate surface prepared in Example 1 of this invention.
[0031] Figure 2 This is a distribution diagram of Escherichia coli colonies on the surface of the TiN sample and the titanium substrate prepared in Example 1 of the present invention.
[0032] Figure 3 The image shows the FE-SEM images of the TiN sample prepared in Example 1 of this invention and the Escherichia coli adhering to the surface of the titanium substrate.
[0033] Figure 4 The images show fluorescence micrographs of Human BMSC cells on the surface of the TiN sample and titanium substrate prepared in Example 1 of this invention.
[0034] Figure 5The image shows the contact angle of the TiN sample and the titanium substrate prepared in Example 1 of this invention.
[0035] Figure 6 This is a distribution diagram of Escherichia coli colonies on the surface of the TiN sample and the titanium substrate prepared in Example 2 of the present invention.
[0036] Figure 7 The image shows the FE-SEM images of the TiN sample and the titanium substrate surface adhered with Escherichia coli prepared in Example 2 of this invention.
[0037] Figure 8 The images show fluorescence micrographs of Human BMSC cells on the surface of the TiN sample and titanium substrate prepared in Example 2 of this invention.
[0038] Figure 9 This is a scratch morphology image of the TiN sample prepared in Example 3 of the present invention.
[0039] Figure 10 The wear profile curves of the TiN sample and 201 austenitic stainless steel prepared in Example 3 of this invention are shown.
[0040] Figure 11 The distribution of Escherichia coli colonies on the surface of the TiN sample and titanium substrate prepared in Example 4 of this invention. Example
[0041] The present invention will be further described below with reference to embodiments. It should be understood that the embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0042] This invention provides a method for preparing a nitrided-TiN composite coating with both mechanical and biological properties on a medical metal surface, comprising the following steps:
[0043] (1) Substrate preparation and pretreatment: After grinding and polishing, the substrate is placed in anhydrous ethanol for ultrasonic cleaning. The air-dried substrate is sent into the coating equipment chamber and the moisture, trace gases and volatile impurities adsorbed on the substrate surface are removed by repeated heating and vacuuming.
[0044] (2) Ion cleaning: The substrate is ion cleaned using arc-enhanced glow discharge technology. The cathode target is a Ti target with a purity of 99.99%. High-purity Ar is introduced to maintain the chamber pressure at 1×10⁻⁶. -4 ~1×10 -2 mbar;
[0045] (3) Low-pressure plasma nitriding: The substrate is nitrided using low-pressure plasma nitriding technology. High-purity N2, high-purity H2 and high-purity Ar are continuously introduced into the chamber while maintaining a suitable constant gas pressure and temperature in the chamber. The substrate is subjected to a negative bias and plasma nitriding is performed for 45 to 90 minutes.
[0046] (4) In-situ integrated coating treatment: A TiN composite coating with excellent biocompatibility and antibacterial adhesion is prepared on the surface of the nitrided substrate by using high-power pulsed magnetron sputtering technology or a hybrid deposition coating technology of plasma-assisted electric arc and high-power pulsed magnetron sputtering.
[0047] This invention also provides a medical metal with a nitriding-TiN composite coating on its surface, wherein the nitriding-TiN composite coating is prepared using the method described above. The medical metal substrate is austenitic stainless steel, titanium, or a metal alloy, and is used in medical metal implants. It maintains excellent biocompatibility and antibacterial adhesion while significantly improving the wear resistance and durability of the implant.
[0048] Example 1
[0049] A method for preparing a nitrided TiN composite coating with both mechanical and biological properties on a medical metal surface, wherein the substrate is a titanium sheet and the coating deposition technology is high-power pulsed magnetron sputtering (HiPIMS) technology, and the specific steps include the following:
[0050] (1) Preparation of substrate sample: The substrate used is pure titanium sheet that has been ground and polished.
[0051] (2) Matrix cleaning: The matrix sample was thoroughly cleaned using an ultrasonic cleaner. It was ultrasonically cleaned in anhydrous ethanol for 15 minutes to remove dirt and oil stains from the matrix surface, and then dried with a hair dryer.
[0052] (3) Matrix Heating and Vacuuming: After the sample is fixed on the planetary support and placed into the chamber, moisture, gas, and organic matter adsorbed on the chamber and sample surface are effectively removed through two heating and vacuuming processes. First, the chamber is evacuated to a vacuum level of 4.0 × 10⁻⁶. -5 Below mbar, the first heating temperature is 600℃ for 30–60 minutes, followed by evacuation of the chamber to a vacuum level of 4.0 × 10⁻⁶ mbar. -5 For temperatures below mbar, the second heating temperature is 550℃, and the time is 30–60 min.
[0053] (4) Ion Cleaning: AEGD technology is used to perform ion cleaning on the substrate to remove surface dust, organic dirt, and oxides. The cathode target used for ion cleaning is a Ti target with a purity of 99.99%, and Ar gas is introduced to maintain the chamber pressure at 1×10⁻⁶. -2 mbar, substrate bipolar bias voltage during ion cleaning is -300 / +20V, target current is 65A, temperature is 500℃, duration is 5min.
[0054] (5) Low-pressure plasma nitriding: After ion cleaning of the substrate surface, high-purity N2, high-purity H2 and high-purity Ar are simultaneously and continuously introduced into the reactor. The target current is 65A, the substrate bias voltage is -300V, the furnace temperature is 600℃, the N2 flow rate is 25sccm, the H2 flow rate is 50sccm and the Ar flow rate is 120sccm.
[0055] This step involves parameter control that differs from the existing conventional N2:H2 ratio (e.g., 1:1). Increasing the H2 proportion is advantageous in this invention. Experiments have shown that controlling the H2 flow rate to be more than 20 sccm higher than the N2 flow rate yields significantly better results than existing technologies. This is because H2 can reduce oxides on the substrate surface, activate plasma, enhance the penetration depth of active nitrogen atoms, and regulate the hardness of the nitrided layer. Finally, the nitriding treatment lasts for 90 minutes.
[0056] (6) Coating Deposition: After low-pressure plasma nitriding, a TiN coating was deposited on the substrate surface in situ using high-power pulsed magnetron sputtering. The sputtering target was a Ti target (purity 99.99%), the average power was 7kW, the pulse on-time and pulse off-time were 60 / 1000μs, the magnetic field strength was 50mT, the N2 flow rate was 140sccm, and the Ar flow rate was 20sccm. Since excessively high substrate bias voltage would lead to excessive residual stress in the coating, which is not conducive to adhesion to the titanium substrate surface, and excessively low substrate bias voltage would also be not conducive to enhancing the coating cohesion, the substrate bias voltage was selected as -100V, the temperature was 550℃, and the deposition time was 120min to ensure the coating adhesion effect.
[0057] (7) Cooling and sampling: After the above steps are completed, turn off the power and wait for the chamber temperature to drop below 70°C. Open the chamber and take out the sample. The substrate surface is a TiN coating with excellent biocompatibility and antibacterial adhesion.
[0058] Comparative experimental results, AFM morphology characterization: the 3D morphology observation scanning range of the coating and titanium substrate is 5μm×5μm. Figure 1 The AFM morphology images of the TiN sample and titanium substrate obtained in Example 1 show that the surface of the titanium substrate is relatively rough, while the surface of the TiN coating deposited by HiPIMS technology is uniform, smooth and dense.
[0059] Colony distribution: The antibacterial effect of TiN-coated samples against *Escherichia coli* was evaluated using the surface spreading plate method. The cultured bacterial stock solution was diluted with PBS to a concentration of 10⁻⁶. 6CFU / mL, the sample was placed in a 48-well plate, and 500 μL of diluted bacterial suspension was added. The mixture of bacterial suspension and sample was then incubated in a 37°C biochemical incubator for 24 h. The sample was then gently removed with sterile forceps and immersed in a centrifuge tube containing 2 mL of PBS. The sample was then sonicated for 8 min to detach bacteria from the sample surface. Finally, 50 μL of bacterial suspension was evenly spin-spread onto a solid agar plate and incubated at 37°C until the appropriate colony size was reached, followed by photographing. Four replicates were prepared for each sample group. Figure 2 The colony distribution of E. coli on the TiN and titanium samples obtained in this embodiment shows that the TiN sample exhibits excellent antibacterial adhesion properties, and the TiN coating acts as a physical barrier to prevent bacteria from directly adhering to the surface of the titanium sheet.
[0060] Tissue characterization: High-resolution field emission scanning electron microscopy was used to observe Escherichia coli (E. coli) adhering to the coating surface. Figure 3 The FE-SEM images of the E. coli distribution on the TiN sample and titanium substrate obtained in this embodiment show that the E. coli are all rod-shaped with a diameter of approximately 400 nm to 2.2 μm. The number of E. coli on the TiN sample surface is significantly reduced compared to the titanium substrate, indicating that the TiN coating has excellent antibacterial adhesion properties. This is related to the low surface roughness of the coating. Lower surface roughness can reduce the formation of bacterial plaques and enhance the stable soft tissue sealing around the substrate.
[0061] Human BMSC nuclear membrane staining assay: After co-culturing the sample with BMSC cells for 24 h, the sample was washed twice with PBS, fixed with 4% paraformaldehyde for 15 min, and washed twice with PBS. Cellmask stock solution was diluted 1:2000 with PBS, and 200 μL of staining agent was added to each well, staining for 10 min at room temperature. After washing three times with PBS, hochest stock solution was diluted 1:1000 with PBS, and 200 μL of staining agent was added to each well, staining for 10 min at room temperature. After the set time, 100 μL of PBS was added to each well to wash the cells twice, and then the position and morphology of the nuclear membrane were observed and photographed under a fluorescence microscope. Figure 4Fluorescence micrographs of Human BMSCs on the TiN sample and titanium substrate surface in this embodiment show that all cells exhibit typical Human BMSC morphology, and various pseudopodia of the cells are well extended on all coating surfaces. The cells present a slender spindle-shaped morphology, with filaments extending in different directions. The TiN sample shows a significantly higher number of adherent cells compared to the titanium substrate, which is related to the high surface energy of the coating. Higher surface energy results in better hydrophilicity, which is more conducive to cell adhesion and proliferation. This indicates that TiN not only enhances cell adhesion on titanium implants but also promotes cell proliferation to a certain extent.
[0062] Contact angle test: The surface tension and surface contact angle tester measures the contact angle of the sample surface, using distilled water as the medium. Figure 5 The images show the contact angles of the TiN sample and the titanium substrate prepared in Example 1 of this invention. It can be seen that the contact angles of the TiN sample and the titanium substrate are 64.8° and 81.8°, respectively. The TiN sample has a smaller surface contact angle and better hydrophilicity, which is related to its lower surface roughness.
[0063] Example 2
[0064] This invention discloses a method for preparing a nitrided TiN composite coating on a medical metal surface that possesses both mechanical and biological properties. The substrate is a pure titanium sheet, and the coating deposition employs a hybrid deposition technique. The specific steps include the following:
[0065] (1) Preparation of matrix sample: Same as in Example 1.
[0066] (2) Matrix cleaning: Same as in Example 1.
[0067] (3) Substrate heating and vacuuming: Same as in Example 1.
[0068] (4) Ion Cleaning: AEGD technology is used to perform ion cleaning on the substrate to remove surface dust, organic dirt, and oxides. The cathode target used for ion cleaning is a Ti target with a purity of 99.99%, and Ar gas is introduced to maintain the chamber pressure at 1×10⁻⁶. -3 mbar, substrate bipolar bias voltage during ion cleaning is -200 / +20V, target current is 95A, temperature is 400℃, duration is 20min.
[0069] (5) Low-pressure plasma nitriding: The target current is 70A, the substrate is negatively biased at -200V, and the furnace temperature is 500℃. High-purity N2, high-purity H2, and high-purity Ar are continuously introduced into the chamber. The N2 flow rate is 20 sccm, the H2 flow rate is 55 sccm, and the Ar flow rate is 160 sccm. Unlike the conventional N2:H2 ratio (e.g., 1:1), this invention increases the H2 ratio, and the H2 flow rate is more than twice that of N2. The nitriding treatment is carried out for 90 minutes.
[0070] (6) Coating deposition: After nitriding, TiN coating is deposited on the substrate surface in situ using hybrid coating technology. Both the sputtering target and the arc target were Ti targets with a purity of 99.99%, and the working gas was Ar with a purity of 99.99%. During the APA-Arc deposition process, the substrate bias was -100V, the target current was 130A, the deposition time was 60Ah, the N2 flow rate was 60sccm, and the Ar flow rate was 80sccm. During the APA-Arc and HiPIMS co-deposition process, the substrate bias was -200V, the deposition time was 100Ah, the N2 flow rate was 60sccm, and the Ar flow rate was 80sccm. During the HiPIMS deposition process, the average power was 7kW, the pulse on-time and pulse off-time were 40 / 1000μs, the substrate bias was -200V, the infrared heating tube temperature was set to 500℃, the deposition time was 60min, the N2 flow rate was 20sccm, and the Ar flow rate was 120sccm.
[0071] The hybrid coating technology combining plasma-assisted arc (APA-Arc) and high-power pulsed magnetron sputtering (HiPIMS) involves three deposition processes: first, a layer is deposited using the APA-Arc module; then, a layer is deposited simultaneously using both the APA-Arc and HiPIMS modules; and finally, a final layer is deposited using the HiPIMS module. The resulting composite coating exhibits significantly higher adhesion and wear resistance than existing methods.
[0072] (7) Cooling and Sampling: After completing the above steps, turn off the power and wait for the chamber temperature to drop below 70°C. Then, open the chamber and remove the sample. The substrate surface will then be a TiN coating with excellent biocompatibility. The TiN coating deposited using the hybrid deposition technique has a uniform, smooth, and dense surface with a coating adhesion of approximately 50 N.
[0073] Comparative experimental results, colony distribution: The experimental method is the same as in Example 1. Figure 6 The images show the colony distribution of E. coli on the TiN sample and the titanium substrate after incubation in Example 2. It can be seen that the TiN sample has fewer colonies than the titanium substrate, demonstrating good antibacterial adhesion properties.
[0074] Tissue characterization: The testing method is the same as in Example 1. Figure 7 The images show the FE-SEM images of the E. coli distribution on the TiN sample and the titanium substrate obtained in Example 2. It can be seen that the number of E. coli on the TiN sample surface is reduced to a certain extent compared with that on the titanium substrate. The E. coli all exhibit a rod-shaped morphology with a diameter of approximately 400 nm to 2.2 μm.
[0075] Human BMSC cell nuclear membrane staining assay: The experimental method is the same as in Example 1. Figure 8 Fluorescence micrographs of Human BMSCs on the TiN sample and titanium substrate surface were obtained for Example 2. All cells exhibited typical Human BMSC morphology, and various pseudopodia of the cells were well extended on all coating surfaces. The cells displayed a slender spindle-shaped morphology, with filaments extending in different directions. The TiN sample showed a certain increase in the number of adherent cells compared to the titanium substrate, which is related to the high surface energy of the coating. Higher surface energy results in better hydrophilicity, which is more conducive to cell adhesion and proliferation. This indicates that the TiN sample is beneficial for enhancing cell adhesion on the titanium implant and also promotes cell proliferation to a certain extent. TiN coatings prepared by conventional single arc ion plating or DC magnetron sputtering techniques often have poor cell adhesion and proliferation effects due to the large surface roughness and high hydrophobicity.
[0076] Example 3
[0077] A method for preparing a nitrided-TiN composite coating with both mechanical and biological properties on a medical metal surface, wherein the substrate is 201 austenitic stainless steel, and the coating deposition technology is high-power pulsed magnetron sputtering (HiPIMS) technology, the specific steps of which include the following:
[0078] (1) Preparation of the substrate sample: 201 austenitic stainless steel was selected as the substrate and was ground and polished.
[0079] (2) Matrix cleaning: The matrix sample was thoroughly cleaned using an ultrasonic cleaner. It was ultrasonically cleaned in anhydrous ethanol for 15 minutes to remove dirt and oil stains from the matrix surface, and then dried with a hair dryer.
[0080] (3) Matrix Heating and Vacuuming: After the sample is fixed on the planetary support and placed into the chamber, moisture, gas, and organic matter adsorbed on the chamber and sample surface are effectively removed through two heating and vacuuming processes. First, the chamber is evacuated to a vacuum level of 4.0 × 10⁻⁶. -5 Below mbar, the first heating temperature is 580℃ for 30–60 minutes, followed by evacuation of the chamber to a vacuum level of 4.0 × 10⁻⁶ mbar. -5 For temperatures below mbar, the second heating temperature is 530℃, and the time is 30–60 min.
[0081] (4) Ion Cleaning: AEGD technology is used to perform ion cleaning on the substrate to remove surface dust, organic dirt, and oxides. The cathode target used for ion cleaning is a Ti target with a purity of 99.99%, and Ar gas is introduced to maintain the chamber pressure at 1×10⁻⁶. -3 mbar, substrate bipolar bias voltage of -250 / +20V, target current of 80A, temperature of 300℃, duration of 20min during ion cleaning.
[0082] (5) Low-pressure plasma nitriding: The process gas introduction process is the same as in Example 1, with a target current of 80A, a substrate bias voltage of -300V, a furnace temperature of 450℃, an N2 flow rate of 20 sccm, an H2 flow rate of 55 sccm, and an Ar flow rate of 160 sccm. Unlike the existing conventional N2:H2 ratio (e.g., 1:1), this invention increases the H2 proportion, which is advantageous because H2 can reduce oxides on the substrate surface, activate the plasma, enhance the penetration depth of active nitrogen atoms, and regulate the hardness of the nitrided layer. The nitriding treatment is performed for 45 minutes.
[0083] (6) Coating deposition: After nitriding, a TiN coating was deposited on the substrate surface in situ using high-power pulsed magnetron sputtering. The sputtering target was a Ti target (purity 99.99%), the average power was 5kW, the pulse on-time and pulse off-time were 20 / 1000μs, the magnetic field strength was 45mT, the N2 flow rate was 110sccm, and the Ar flow rate was 20sccm. Since excessively high substrate bias voltage would lead to excessive residual stress in the coating and would not be conducive to adhesion on the titanium substrate surface, while excessively low substrate bias voltage would also not be conducive to enhancing the coating cohesion, the substrate bias voltage was selected as -300V, the temperature was 400℃, and the deposition time was 240min to ensure the coating adhesion effect.
[0084] (7) Cooling and sampling: Same as in Example 1.
[0085] Comparative test results: Scratch test: The adhesion performance of the coating was tested using a high-load scratch tester. The initial load was 0.3N, the maximum applied load was 80N, the loading rate was 50N / min, the indenter sliding speed was 5mm / min, and the scratch length was 7.97mm. Figure 9 The image shows the scratch morphology of the TiN coating obtained in Example 3. The arrows indicate the scratch direction. When the load increases to 49.6 N, a small amount of peeling begins to occur, indicating that the coating adhesion is 49.6 N, which meets the current requirements for high adhesion in the field of surface modification coatings for medical implants. The high adhesion of the coating is related to the AEGD ion cleaning pretreatment of the substrate surface, and the multi-layer coating structure resulting from the low-pressure plasma nitriding pretreatment reduces stress accumulation and forms a gradient distribution, thereby improving the load-bearing capacity. The deposited TiN coating has a uniform, smooth, and dense surface with an adhesion of approximately 50 N.
[0086] Friction and wear test: The friction and wear properties of the substrate and TiN coating were analyzed and characterized using a multi-functional friction and wear tester, and the cross-sectional profile of the wear track was characterized using a RTEC-INSTRUMENTS multi-functional profiler. Figure 10The wear trajectory profile curves of the TiN coating and the substrate obtained in Example 3 show that, compared with the uncoated 201 austenitic stainless steel substrate, the wear rate of the sample after TiN coating deposition is significantly reduced, indicating that the TiN coating has excellent wear resistance. The high hardness may be the reason for its good wear resistance.
[0087] Example 4
[0088] A method for preparing a nitrided TiN composite coating with both mechanical and biological properties on a medical metal surface, wherein the substrate is a pure titanium sheet and the coating deposition technology is a hybrid technology, and the specific steps include the following:
[0089] (1) Preparation of matrix sample: Same as in Example 1.
[0090] (2) Matrix cleaning: Same as in Example 1.
[0091] (3) Substrate heating and vacuuming: Same as in Example 1.
[0092] (4) Ion Cleaning: AEGD technology is used to perform ion cleaning on the substrate to remove surface dust, organic dirt, and oxides. The cathode target used for ion cleaning is a Ti target with a purity of 99.99%, and Ar gas is introduced to maintain the chamber pressure at 1×10⁻⁶. -3 mbar, substrate bipolar bias voltage during ion cleaning is -250 / +20V, target current is 80A, temperature is 600℃, duration is 10min.
[0093] (5) Low-pressure plasma nitriding: After ion cleaning of the substrate surface, high-purity N2, high-purity H2 and high-purity Ar are simultaneously and continuously introduced into the reactor. The target current is 65A, the substrate bias voltage is -300V, the furnace temperature is 550℃, the N2 flow rate is 20sccm, the H2 flow rate is 55sccm, the Ar flow rate is 160sccm, and the nitriding treatment is carried out for 90min.
[0094] (6) Coating deposition: After nitriding, TiN coating is deposited on the substrate surface in situ using hybrid coating technology. Both the sputtering target and the arc target were Ti targets with a purity of 99.99%, and the working gas was Ar with a purity of 99.99%. During the APA-Arc deposition process, the substrate bias was -300V, the target current was 100A, the deposition time was 35Ah, the N2 flow rate was 35sccm, and the Ar flow rate was 105sccm. During the APA-Arc and HiPIMS co-deposition process, the substrate bias was -300V, the deposition time was 70Ah, the N2 flow rate was 40sccm, and the Ar flow rate was 100sccm. During the HiPIMS deposition process, the average power was 3kW, the pulse on-time and pulse off-time were 20 / 1000μs, the substrate bias was -50V, the infrared heating tube temperature was set to 400℃, the deposition time was 120min, the N2 flow rate was 40sccm, and the Ar flow rate was 100sccm.
[0095] The hybrid coating technology combining plasma-assisted arc (APA-Arc) and high-power pulsed magnetron sputtering (HiPIMS) involves three deposition processes: first, a layer is deposited using the APA-Arc module; then, a layer is deposited simultaneously using both the APA-Arc and HiPIMS modules; and finally, a final layer is deposited using the HiPIMS module. The resulting composite coating exhibits significantly higher adhesion and wear resistance than existing methods.
[0096] (7) Cooling and sampling: Same as in Example 1.
[0097] Comparative test results show that the TiN coating deposited using the hybrid deposition technology has a uniform, smooth, and dense surface with a coating adhesion of approximately 50 N.
[0098] Colony distribution: The experimental method is the same as in Example 1. Figure 11 The images show the colony distribution of E. coli on the TiN sample obtained in Example 4 and on the titanium substrate after incubation. It can be seen that the TiN coating prepared using the Hybrid technology in this example has fewer colonies than the titanium substrate, exhibiting good antibacterial adhesion properties.
[0099] This invention discloses a method for preparing a nitriding-TiN composite coating on medical metal surfaces that possesses both mechanical and biological properties. The method is practical and easy to operate, and can comprehensively improve the adhesion, wear resistance, and biocompatibility of the nitriding-TiN coating on medical metal surfaces. Medical metals with the nitriding-TiN coating of this invention are used in medical metal implants, maintaining excellent biocompatibility and antibacterial adhesion while significantly improving the wear resistance and durability of the implant.
Claims
1. A method for preparing a nitriding-TiN composite coating with both mechanical and biological properties on a medical metal surface, comprising the following steps: (1) Substrate preparation and pretreatment: the substrate is ground and polished and then placed in anhydrous ethanol for ultrasonic cleaning. The air-dried substrate is sent into the coating equipment chamber and the moisture, trace gases and volatile impurities adsorbed on the substrate surface are removed by repeated heating and vacuuming. (2) Ion cleaning: The substrate is ion cleaned using arc-enhanced glow discharge technology. The cathode target is a Ti target with a purity of 99.99%. High-purity Ar is introduced to maintain the chamber pressure at 1×10⁻⁶. -4 ~1×10 -2 mbar; (3) Low-pressure plasma nitriding treatment: The substrate is nitrided using low-pressure plasma nitriding technology. High-purity N2, high-purity H2 and high-purity Ar are continuously introduced into the chamber. The flow rate of H2 is more than 20 sccm higher than that of N2. At the same time, the appropriate gas pressure in the chamber is kept constant at 0.15 to 2.0 Pa and the temperature is kept constant at 450 to 600 °C. The substrate is subjected to a negative bias voltage of -50 to -400 V for 45 to 90 min of plasma nitriding treatment. (4) In-situ integrated coating treatment: A TiN composite coating with excellent biocompatibility and antibacterial adhesion is prepared on the surface of the nitrided substrate by using high-power pulsed magnetron sputtering technology or a hybrid deposition coating technology of plasma-assisted electric arc and high-power pulsed magnetron sputtering.
2. The method according to claim 1, characterized in that: In step (1), the chamber is heated and evacuated twice. First, the chamber is evacuated to a vacuum level of 4.0 × 10⁻⁶. -5 Below mbar, heat at 550~600 ℃ for 30~60 min, then evacuate the chamber to a vacuum of 4.0×10. -5 Below mbar, heat at 500~550 ℃ for 30~60 min.
3. The method according to claim 1, characterized in that: In step (2), the planetary carrier bipolar bias voltage used in ion cleaning is -200~-300 / +20 V, the target current is 65~95 A, the temperature is 300~600 ℃, and the duration is 5~20 min.
4. The method according to claim 1, characterized in that: In step (3), the arc target that serves as the electron source is a Ti target with a purity of 99.99% and a target current of 65~95 A; the planetary carrier on which the substrate is placed is connected to the negative terminal of the pulse power supply with a negative bias voltage of -50~-400 V, using a bipolar pulse with a frequency of 15~25 kHz and a duty cycle of 65%~95%; The ion nitriding temperature is 450~600 ℃, the gas pressure is 0.15~2.0 Pa, the N2 flow rate is 20~55 sccm, the H2 flow rate is 20~55 sccm, and the Ar flow rate is controlled by the gas pressure to be 120~190 sccm.
5. The method according to claim 1, characterized in that: In step (4), when using high-power pulsed magnetron sputtering (HiPIMS) for coating, the sputtering target is a Ti target with a purity of 99.99%, and the working gas is Ar with a purity of 99.99% and N2 with a purity of 99.99%. The target-substrate distance is controlled to be 85~90 mm. During coating, the gas input is controlled by flow rate, with the total flow rate maintained at 130~180 sccm, the average power being 5~7 kW, the pulse on-time and pulse off-time being 20~60 / 1000 μs, the magnetic field strength being 45~50 mT, the substrate bias voltage being -100~-300 V, the temperature of the infrared heating tube being set to 400~550 ℃, and the deposition time being 120~240 min.
6. The method according to claim 1, characterized in that: In step (4), when plasma-assisted arc (APA-Arc) and high-power pulsed magnetron sputtering (HiPIMS) are used for mixed deposition coating, both the sputtering target and the arc target are Ti targets with a purity of 99.99%, the working gas is Ar with a purity of 99.99% and N2 with a purity of 99.99%, and the target-substrate distance is 85~90 mm; the mixed deposition coating includes APA-Arc deposition process, APA-Arc and HiPIMS co-deposition process, and HiPIMS deposition process.
7. The method according to claim 6, characterized in that: During the APA-Arc deposition process, the substrate bias voltage is -50 to -300V, the target current is 100 to 140 A, the deposition time is 40 to 70 h, the N2 flow rate is 35 to 70 sccm, and the Ar flow rate is controlled to make the total gas pressure 0.9 to 1 Pa. During the co-deposition of APA-Arc and HiPIMS, the matrix bias is -200 to -300 V, the deposition time is 70 to 110 h, the N2 flow rate is 40 to 70 sccm, and the Ar flow rate is controlled to make the total gas pressure 0.9 to 1 Pa. During the HiPIMS deposition process, the average power is 3~7 kW, the pulse on-time and pulse off-time are 20~60 / 1000μs, the magnetic field strength is 45~50 mT, the substrate bias voltage is -50~-300 V, the infrared heating tube temperature is set to 400~550 ℃, the deposition time is 60~120 min, the N2 flow rate is 20~40 sccm, and the Ar flow rate is controlled to make the total gas pressure 0.55~0.68 Pa.
8. A medical metal with a surface-deposited nitriding-TiN composite coating, characterized in that: A low-pressure plasma nitriding-TiN composite coating was prepared using the method described in claim 1.
Citation Information
Patent Citations
Titanium alloy surface coating and preparation method thereof
CN115074796B
Arc plasma assisted low-pressure nitriding method under different atmospheres
CN105154816A
Method for depositing film through high ionization rate high power pulse magnetron sputtering
CN105154838A